The Effect of Knowledge of Human Rights Concepts on Global Diversity in FKIP University Riau Students - Rahmita Firda Zain; Jumili Arianto; Mirza Hardian (CV. Rayyan Dwi Bharata, 2023)
This research is motivated by a lack of tolerance as a form of global diversity among the community and students. This study aims to determine whether there is an influence of knowledge of the concept of human rights on global diversity in FKIP students at the University of Riau. This study used a quantitative research method with a causal associative approach, and involved students of the Teaching and Education Faculty of the University of Riau as research subjects. The data collection instrument used was a questionnaire, data processing used the IBM SPSS Version 25 application. Based on the results of the analysis, a simple linear regression equation was obtained, namely Å¶ = 10.904 + 0.381X, the regression coefficient X was 0.381 which stated that an addition of 1% value of human rights concept knowledge, then global diversity will increase by 0.381. Furthermore, the results of the t test obtained t_count (10.904) t_table (1.98) which shows that Ho is rejected and Ha is accepted. Thus, the research hypothesis is accepted that there is an influence of knowledge of the concept of human rights on global diversity in FKIP students at the University of Riau.